2009
DOI: 10.1007/s11666-009-9419-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Splat-Substrate Interface for a NiCr Coating Plasma Sprayed onto Polished Aluminum and Stainless Steel Substrates

Abstract: In the plasma spraying process, the mechanisms by which molten particles impact on and bond with the substrate are not fully understood. For this study a nickel-chromium powder was sprayed onto mirror polished aluminum 5052 and stainless steel 304 substrates to form single splats. The splats and their interface with the substrate were studied using detailed microstructural characterization with emphasis on the shape of the splats, the nature of the splat-substrate interface, including the degree of contact and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Nickel and stainless steel have the similar lattice parameters and crystal structures, resulting in grain growth between two phases across the interface. The studies, not shown here [32], found that NiCr and stainless steel grains were juxtaposed with the same orientation across the interface. Thus, all these studies, with evidence of diffusion and jetting, suggested that substrate melting has occurred.…”
Section: Tem Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Nickel and stainless steel have the similar lattice parameters and crystal structures, resulting in grain growth between two phases across the interface. The studies, not shown here [32], found that NiCr and stainless steel grains were juxtaposed with the same orientation across the interface. Thus, all these studies, with evidence of diffusion and jetting, suggested that substrate melting has occurred.…”
Section: Tem Resultsmentioning
confidence: 68%
“…A trace of iron oxide and chromium oxide was observed at the splat-substrate interface where substrate melting occurred. Selected area diffraction patterns were also used in this study (not shown here) [32], to determine the structure of the oxide. Through a range of diffraction analysis, a number of oxides including NiO, Cr 2 O 3 or CrO 3 and FeO were observed.…”
Section: Tem Resultsmentioning
confidence: 99%
“…Melting-Induced Splashing Model. As proposed by the previous researchers, thermal sprayed coating was always mechanical bonded with the substrate [52][53][54][55][56]; however, the substrate melting at the splat-substrate interface during splat collection process was also reported recently with both experimental and numerical simulation [23,78,101,[109][110][111][112][113].…”
Section: Substratementioning
confidence: 99%
“…Zhang et al [101] also detected an intermetallic layer between the molybdenum splat and the mild steel substrate and suggested that substrate melting occurred. Melting of the substrate, along with intermixing and diffusion between substrate and splat materials, was found when the nickel-chromium powder was thermally sprayed onto the �at stainless steel 304 substrate, but not for the aluminum substrate [78,[111][112][113]. Figure 6 [23].…”
Section: Substratementioning
confidence: 99%
“…Thermal spraying technologies are widely used to produce various coatings with high deposition rate for structural and functional applications, which certainly give much greater flexibility and could easily be adapted to deposit coatings onto components surface having very different geometries . It allows using the widest range of available materials to obtain different coatings for the application in many industrial fields, such as wear resistance coatings, thermal barrier coatings, and resistance corrosive environment coatings .…”
Section: Introductionmentioning
confidence: 99%